The MtZ Strain: Molecular Characteristics and Outbreak Investigation of the Most Successful Mycobacterium tuberculosis Strain in Aragon Using Whole-Genome Sequencing - Comín, Jessica; Madacki, Jan; Rabanaque, Isabel; Zúñiga-Antón, María; Ibarz, Daniel; Cebollada, Alberto; Viñuelas, Jesús; Torres, Luis; Sahagún, Juan; Klopp, Christophe; Gonzalo-Asensio, Jesús; Brosch, Roland; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Since 2004, a tuberculosis surveillance protocol has been carried out in Aragon, thereby managing to detect all tuberculosis outbreaks that take place in the community. The largest outbreak was caused by a strain named MtZ, causing 242 cases as of 2020. The main objective of this work is to analyze this outbreak and the molecular characteristics of this successful strain that could be related to its greater virulence. To do this, we first applied whole genome sequencing to 57 of the isolates. This revealed two principal transmission clusters and six sub-clusters arising from them. The MtZ strain belongs to L4.8 and had eight specific SNPs in genes considered to be virulence factors (ptpA, mc3D, mc3F, VapB41, pks15 (two SNPs), virS and VapC50). Second, a transcriptomic study was carried out to better understand the multiple IS6110 copies present in its genome. This allowed us to observe three effects of IS6110: the disruption of the gene in which the IS6110 is inserted (desA3), the overexpression of a gene (ppe38) and the absence of transcription of genes (cut1:Rv1765c) due to the recombination of two IS6110 copies. Finally, because of the disruption of ppe38 and ppe71 genes by an IS6110, a study of PE_PGRS secretion was carried out, showing that MtZ secretes these factors in higher amounts than the reference strain, thereby differing from the hypervirulent phenotype described for the Beijing strains. In conclusion, MtZ consists of several SNPs in genes related to virulence, pathogenesis and survival, as well as other genomic polymorphisms, which may be implicated in its success among our population.